Strengthening the Entrepreneurial Spirit and Digital Marketing of the Suana Coconut Shell SMEs in Banjar Koripan Kangin, Banjarangkan, Klungkung - Martadiani, Anak Agung Media; Surasmi, Ida Ayu; Suarka, Ida Bagus Komang (Asian Journal of Community Services, 2024)
Coconut shells can be used to create high-value craft products, but artisans often face challenges like a lack of entrepreneurial spirit, limited online marketing knowledge, and poor book-keeping skills. To address these issues, a community partnership program was implemented with Mr. Nyoman Suana, a coconut shell artisan in Banjar Koripan Kangin, Banjarangkan, Klungkung. The program aimed to boost sales and improve book-keeping practices through three main activities: online marketing assistance, entrepreneurial spirit enhancement sessions, and book-keeping training. The results showed that participants successfully utilized social media for marketing, improved their book-keeping, reducing errors, and developed a more innovative and responsible entrepreneurial mindset